A high-strength and toughness metal ceramic and preparation method thereof

By introducing hard phases, adhesion, and metal enhanced agents in metal ceramic tools, adopting diffuse reinforcement and solid -soluble enhanced technology, solving the problem of poor anti -collapse damage at high -temperature and high -speed cutting conditions, achieved hardness, and achieved hardness, which Improvement of toughness and abrasion resistance.

CN118880144BActive Publication Date: 2025-01-24GANZHOU ACHTECK TOOL TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411382968.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-24
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing metal cermet tools have poor collapse resistance under high temperature and high speed cutting conditions, and are prone to sudden collapse, affecting the tool life and surface finish of the processed parts.

Method used

A high-strength and tough cermet is used, which includes a hard phase, a bonding phase and a metal strengthener. The hard phase is composed of titanium-based carbides, nitrides or nitrogen carbides. The bonding phase contains transition metals cobalt, nickel and iron. The metal strengthening agent contains tantalum, niobium, manganese and other elements. Through dispersion strengthening and solid solution Strengthening technology improves the comprehensive performance of materials.

Benefits of technology

It significantly improves the hardness, toughness, high temperature stability and abrasion resistance of metal ceramics, extended the service life of the tool, and improved the surface smoothness of the processing container.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118880144B_ABST
    Figure CN118880144B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal ceramics, and relates to a high-strength and toughness metal ceramic and a preparation method thereof, which comprises: a hard phase, which comprises carbides, nitrides, nitrogen carbides or a combination thereof of at least one metal element in the IVB, VB, and VIB groups of the periodic table with titanium as the main element; a bonding phase, which comprises at least two of transition metals cobalt, nickel, and iron; a metal reinforcing agent, which comprises at least two of tantalum, niobium, manganese, ruthenium, rhenium, yttrium, and cerium, and the metal reinforcing agent is distributed in a refined and uniformly dispersed state in the microstructure of the metal ceramic; wherein, in the hard phase, there are dispersion-strengthened hard phase precipitates formed by the reaction of metal elements in part of the metal reinforcing agent with carbon, and the metal elements in another part of the metal reinforcing agent are solid-dissolved in the bonding phase to form a solid-solution-strengthened bonding phase. The present invention improves the comprehensive performance of metal ceramics through hard phase dispersion strengthening and bonding phase solid-solution strengthening.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal ceramics, and specifically relates to a high-strength and toughness metal ceramic and a preparation method thereof. Background Art

[0002] As an upgraded alternative material for cemented carbide materials, Ti(C,N)-based cermets have higher wear resistance, lower friction coefficient between metals, better high temperature performance and oxidation resistance, making cermet tools well adapted to high-speed, high-precision and continuous, dry cutting with larger feed volume, greatly improving cutting efficiency and service life. Ti(C,N)-based cermets are made by powder metallurgy using soft transition metals (Ni, Co) bonded with ceramic matrix phases such as TiC, TiN, Ti(C,N) and secondary carbides (such as Mo2C, WC, TaC, etc.). Compared with cemented carbide tools, Ti(C,N)-based cermets have better affinity for iron and high temperature strength. It is a composite material with high hardness and high wear resistance. The material properties effectively make up for the cutting gaps of cemented carbide and oxide ceramic materials, making it widely used in the field of high-speed precision cutting to obtain good surface finish. With the current demand for increasing processing efficiency, metal ceramics work under high temperature and high speed cutting conditions, and the ceramic characteristics of poor resistance to fracture are highlighted. Sudden fracture is prone to occur, which reduces the tool life and affects the surface finish of the workpiece. In order to obtain ideal yield strength, red hardness, resistance to plastic deformation, wear resistance and other properties, according to the scientific theories of solid solution strengthening, dispersion strengthening, grain boundary strengthening and other scientific theories of material science, the metal ceramic tools and their preparation methods currently used for processing steel materials still need to be improved. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a high-strength and toughness metal ceramic and a preparation method thereof.

[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0005] A high-strength and high-toughness metal ceramic comprising:

[0006] A hard phase comprising a carbide, a nitride, a nitride carbide or any combination thereof of at least one metal element in Groups IVB, VB and VIB of the periodic table, mainly titanium;

[0007] A binder phase comprising at least two of the transition metals cobalt, nickel, and iron;

[0008] A metal strengthener comprising at least two of tantalum, niobium, manganese, ruthenium, rhenium, yttrium and cerium, wherein the metal strengthener is distributed in a refined and uniformly dispersed state in the microstructure of the metal ceramic; wherein in the hard phase there are dispersion-strengthened hard phase precipitates formed by the reaction of a part of the metal elements in the metal strengthener with carbon and precipitation, and another part of the metal elements in the metal strengthener are solid-dissolved in the bonding phase to form a solid-solution-strengthened bonding phase.

[0009] As a preferred embodiment of the high-strength and toughness metal ceramic described in the present invention, the binder phase accounts for 10-24wt% of the total amount of the metal ceramic, and the hard phase accounts for 76-90wt% of the total amount of the metal ceramic.

[0010] As a preferred embodiment of the high-strength and toughness metal ceramic described in the present invention, the particle size of the hard phase is 0.5-5.0 μm, preferably 0.8-2.0 μm.

[0011] As a preferred embodiment of the high-strength and toughness metal ceramic described in the present invention, the metal strengthener includes at least one of tantalum, niobium and manganese, tantalum accounts for 0.35~6.0wt% of the total amount of the metal ceramic, niobium accounts for 0.2~2.0wt% of the total amount of the metal ceramic, and manganese accounts for 0.3~4.0wt% of the total amount of the metal ceramic.

[0012] As a preferred embodiment of the high-strength and toughness metal ceramic described in the present invention, the metal strengthener includes at least one of tantalum, niobium and manganese, tantalum accounts for 0.4~2.4wt% of the total amount of the metal ceramic, niobium accounts for 0.3~0.8wt% of the total amount of the metal ceramic, and manganese accounts for 0.5~2.0wt% of the total amount of the metal ceramic.

[0013] As a preferred embodiment of the high-strength and toughness metal ceramic described in the present invention, the mass ratio of tantalum and niobium added to the binder phase is (1-4):1, preferably 2:1.

[0014] As a preferred embodiment of the high-strength and toughness metal ceramic described in the present invention, the proportion of manganese added to the binder phase in the metal strengthener is ≤50wt%, preferably ≤33.3wt%.

[0015] As a preferred embodiment of the high-strength and toughness metal ceramic described in the present invention, in which: in the same scanning electron microscope photograph, the hard phase includes a first hard phase and a second hard phase, wherein the first hard phase mainly appears as a phase with a black core-gray outer ring structure and a phase with a black-gray structure, and the first hard phase is mainly titanium carbide, titanium nitride, and titanium nitride carbide, and the second hard phase mainly appears as a phase with a bright core-gray outer ring structure; the bonding phase mainly appears as a phase with a medium-brightness structure, and the bonding phase has a large number of point-precipitated micro-nano precipitated phases at the interface of the hard phase.

[0016] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0017] A method for preparing the above-mentioned metal ceramic comprises the following steps:

[0018] S1. Prepare metal strengthening agent;

[0019] S2, preparing hard phase powder and binder phase powder, wherein the hard phase powder comprises carbide, nitride, nitride or any combination thereof of at least one metal element in Groups IVB, VB and VIB of the periodic table with titanium as the main component, and the binder phase powder comprises at least two of the transition metals cobalt, nickel and iron, and then mixing the hard phase powder, the binder phase powder, the metal reinforcing agent, the solvent and the forming agent in step S1, ball milling the mixture again, and then spraying the mixture to obtain the mixture;

[0020] S3, pressing the mixed material into a compact to obtain a green compact;

[0021] S4. Place the pressed green sheet in a sintering furnace, raise the temperature to the forming agent removal temperature according to a predetermined sintering process, and after removing the forming agent, perform micro-pressure atmosphere sintering. During the sintering process, part of the metal particles in the metal reinforcing agent react with carbon and precipitate fine dispersion-strengthened hard phase precipitates. The dispersion-strengthened hard phase precipitates are dispersed in the hard phase. At the same time, another part of the metal particles in the metal reinforcing agent are dissolved in the bonding phase to form a solid solution-strengthened bonding phase, and finally a high-strength and toughness metal ceramic is obtained.

[0022] As a preferred embodiment of the method for preparing a high-strength and toughness metal ceramic of the present invention, in step S1, the metal reinforcement raw material comprises metal powders, oxides, complexes, salts or any combination thereof of at least two metal elements of tantalum, niobium, manganese, ruthenium, rhenium, yttrium and cerium.

[0023] As a preferred embodiment of the method for preparing a high-strength and toughness metal ceramic of the present invention, in which: in step S1, the metal reinforcement raw material is mixed with the forming agent and the solvent, and after ball milling and drying, the material is subjected to hydrogen reduction treatment to obtain ultrafine metal particles as the metal reinforcement, and the particle size of the metal reinforcement is 100~500nm.

[0024] As a preferred embodiment of the method for preparing a high-strength and toughness metal ceramic of the present invention, in step S1, the hydrogen reduction temperature is 400-800°C.

[0025] As a preferred embodiment of the method for preparing a high-strength and toughness metal ceramic of the present invention, wherein: in steps S1 and S2, the molding agent is selected from at least one of 48#~56# paraffin wax and PEG1000~PEG20000; the solvent is selected from at least one of anhydrous ethanol and deionized water.

[0026] As a preferred embodiment of the method for preparing a high-strength and toughness metal ceramic of the present invention, in step S2, the amount of the metal reinforcement added is 0.5-5wt% of the total amount of the metal ceramic, preferably 1.2-3.6%.

[0027] As a preferred embodiment of the method for preparing a high-strength and toughness metal ceramic of the present invention, in step S4, the atmosphere in the sintering furnace during the forming agent removal process is a hydrogen atmosphere or a vacuum atmosphere:

[0028] In step S1, the metal reinforcement raw material is subjected to hydrogen reduction treatment, and the atmosphere in the sintering furnace during the forming agent removal process is a vacuum atmosphere;

[0029] In step S1, when the metal reinforcing agent raw material is directly used, the atmosphere in the sintering furnace during the forming agent removal process is a hydrogen atmosphere.

[0030] As a preferred embodiment of the preparation method of a high-strength and toughness metal ceramic of the present invention, in which: in step S4, the micro-pressure atmosphere sintering is specifically as follows: after heating to temperature A, introducing a process gas of x mbar, then heating and sintering to temperature B in a nitrogen atmosphere at a heating rate of 2~10℃ / min, then switching to vacuum sintering, keeping at temperature B for 0.5~3h, then cooling to 1200℃ in a process gas partial pressure atmosphere of y mbar, and finally high-pressure cooling in an argon atmosphere; wherein, temperature A is 1000~1400℃, temperature B is 1400~1600℃, x is 0.5~60, y is 10~100, and the process gas is at least one selected from nitrogen, argon, and helium.

[0031] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0032] A cutting tool comprises a substrate, wherein the substrate is composed of the metal ceramic or the metal ceramic prepared according to the preparation method.

[0033] The beneficial effects of the present invention are as follows:

[0034] The present invention proposes a high-strength and toughness metal ceramic and a preparation method thereof, which includes: a hard phase, which includes carbides, nitrides, nitrogen carbides or combinations thereof of at least one metal element in Groups IVB, VB, and VIB of the periodic table with titanium as the main component; a bonding phase, which includes at least two of the transition metals cobalt, nickel, and iron; a metal strengthener, which includes at least two of tantalum, niobium, manganese, ruthenium, rhenium, yttrium, and cerium, and the metal strengthener is distributed in the microstructure of the metal ceramic in a refined and uniformly dispersed state; wherein, in the hard phase, there are dispersion-strengthened hard phase precipitates formed by the reaction of part of the metal elements in the metal strengthener with carbon, and another part of the metal elements in the metal strengthener are solid-dissolved in the bonding phase to form a solid-solution-strengthened bonding phase. The present invention improves the comprehensive properties of the metal ceramic, such as hardness, toughness, high-temperature stability, and wear resistance, through dispersion strengthening of the hard phase and solid-solution strengthening of the bonding phase:

[0035] (1) Improved hardness and wear resistance: By introducing carbides, nitrides, nitrogen carbides or combinations of at least one metal element in Groups IVB, VB, and VIB of the periodic table, mainly titanium, into the hard phase, and combining the dispersion-strengthened hard phase precipitates precipitated by the reaction of metal strengtheners and carbon, the hardness and wear resistance of the material are significantly improved.

[0036] (2) Enhanced toughness: At least two of the transition metals cobalt, nickel, and iron are used as the matrix in the bonding phase. These metals have good plasticity and toughness. At the same time, part of the metal reinforcement is dissolved in the bonding phase to form a solid solution strengthened bonding phase, which further improves the strength and toughness of the bonding phase.

[0037] (3) Improve high temperature stability: The metal reinforcement is refined and evenly dispersed in the metal ceramic, which effectively hinders the growth and phase change of grains at high temperatures and improves the thermal stability and creep resistance of the material.

[0038] (4) Improvement of comprehensive performance: Through the design of dual-phase strengthening, namely the dispersion strengthening of the hard phase and the solid solution strengthening of the bonding phase, the comprehensive performance of the metal ceramic, such as hardness, toughness, high temperature stability and wear resistance, is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0040] Figure 1 This is an electron microscope photograph of the internal structure of the metal ceramic of the present invention.

[0041] In the figure, 1-first hard phase, 2-second hard phase, 3-solid solution strengthened bonding phase, 4-micro-nano precipitated phase.

[0042] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0043] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The present invention provides a high-strength and toughness metal ceramic and a preparation method thereof. The solid solution strengthening of the bonding phase is used as a design idea. At the same time, the hardness and high-temperature performance of the material are improved by dispersing, precipitating and carbonizing a slightly supersaturated strengthening metal.

[0045] Ta has good high temperature corrosion resistance, and its atomic radius is large, 15%~18% larger than Ni, Co and Fe atoms. When Co and Ni bonding phase solid solution are added, the lattice constant increases more, and the elastic stress field formed has a greater resistance to dislocation movement; at the same time, Ta can also reduce the stacking fault energy of the γ solid solution. Studies have shown that the strong oxidizing property of tantalum causes tantalum to react chemically with the high temperature stress of the alloy structure to form a new stable compound, while inhibiting the creep of the γ phase, so that the alloy with tantalum added has better high temperature strength than the control group, and its creep rate is reduced by nearly half, so the instantaneous tensile strength and creep performance of the γ solid solution are significantly improved.

[0046] Nb is also one of the commonly used solid solution strengthening elements. The atomic radius is larger than that of W and Mo, and 15~18% larger than that of Ni, Co and Fe atoms. Nb increases the lattice constant more significantly than W and Mo, so the solid solution strengthening effect of Nb is greater. Since Nb significantly reduces the stacking fault energy of the γ matrix, it significantly reduces the creep rate and improves the creep performance. Nb is also a carbide-forming element. On the one hand, it can act as an inhibitor of grain growth and refine the structure; on the other hand, it can disperse the phase and significantly improve the alloy's hot hardness and resistance to thermal shock, hot pressure and oxidation.

[0047] The refractory metal Re has an atomic radius 10% larger than that of Ni. Its chemical properties are similar to those of manganese and technetium. It enters the binder phase as a solid solution, causing lattice distortion, generating an elastic stress field, hindering dislocation movement, and improving the strength of Re-containing alloys.

[0048] Ru performs solid solution strengthening, causing the alloy lattice to expand and generate a long-range stress field, thereby strengthening the alloy. Since Ru is mainly dissolved in the γ phase, the alloy has a large negative mismatch, which prolongs the alloy's life under high temperature and low stress.

[0049] The electron shell distribution of rare earth elements is different from that of traditional elements, which gives them higher coupling energy and strong coordination ability. By filling crystal vacancies and reducing the number of crystal defects, rare earth elements play an important role in the stability and improvement of crystal structure.

[0050] According to one aspect of the present invention, the present invention provides the following technical solution:

[0051] A high-strength and high-toughness metal ceramic comprising:

[0052] A hard phase comprising a carbide, a nitride, a nitride carbide or any combination thereof of at least one metal element in Groups IVB, VB and VIB of the periodic table, mainly titanium;

[0053] A binder phase comprising at least two of the transition metals cobalt, nickel, and iron;

[0054] A metal strengthener comprising at least two of tantalum, niobium, manganese, ruthenium, rhenium, yttrium and cerium, wherein the metal strengthener is distributed in a refined and uniformly dispersed state in the microstructure of the metal ceramic; wherein in the hard phase there are dispersion-strengthened hard phase precipitates formed by the reaction of a part of the metal elements in the metal strengthener with carbon and precipitation, and another part of the metal elements in the metal strengthener is solid-dissolved in the bonding phase to form a solid-solution-strengthened bonding phase.

[0055] Preferably, the binder phase accounts for 10-24 wt % of the total amount of the metal ceramic, and the hard phase accounts for 76-90 wt % of the total amount of the metal ceramic.

[0056] Preferably, the particle size of the hard phase is 0.5 to 5.0 μm, preferably 0.8 to 2.0 μm.

[0057] Preferably, the metal strengthener comprises at least one of tantalum, niobium and manganese, wherein tantalum accounts for 0.35-6.0wt% of the total amount of the metal ceramic, niobium accounts for 0.2-2.0wt% of the total amount of the metal ceramic, and manganese accounts for 0.3-4.0wt% of the total amount of the metal ceramic.

[0058] Preferably, the metal strengthener comprises at least one of tantalum, niobium and manganese, tantalum accounts for 0.4-2.4wt% of the total amount of the metal ceramic, niobium accounts for 0.3-0.8wt% of the total amount of the metal ceramic, and manganese accounts for 0.5-2.0wt% of the total amount of the metal ceramic.

[0059] Preferably, the mass ratio of tantalum and niobium added to the binder phase is (1-4):1, preferably 2:1.

[0060] Preferably, the proportion of manganese added to the binder phase in the metal reinforcement is ≤50wt%, preferably ≤33.3wt%.

[0061] Preferably, Figure 1 As shown, in the same scanning electron microscope photograph, the hard phase includes a first hard phase 1 and a second hard phase 2, wherein the first hard phase 1 mainly appears as a phase with a black core-gray outer ring structure and a phase with a black-gray structure, and the first hard phase 1 is mainly titanium carbide, titanium nitride, and titanium nitride carbide, and the second hard phase 2 mainly appears as a phase with a bright core-gray outer ring structure; the solid solution-strengthened bonding phase 3 mainly appears as a phase with a medium brightness structure, and there are a large number of point-precipitated micro-nano precipitate phases 4 at the interface between the solid solution-strengthened bonding phase 3 and the hard phase.

[0062] According to another aspect of the present invention, the present invention provides the following technical solution:

[0063] A method for preparing the above-mentioned metal ceramic comprises the following steps:

[0064] S1. Prepare metal strengthening agent;

[0065] S2, preparing hard phase powder and binder phase powder, wherein the hard phase powder comprises carbide, nitride, nitride or any combination thereof of at least one metal element in Groups IVB, VB and VIB of the periodic table with titanium as the main component, and the binder phase powder comprises at least two of the transition metals cobalt, nickel and iron, and then mixing the hard phase powder, the binder phase powder, the metal reinforcing agent, the solvent and the forming agent in step S1, ball milling the mixture again, and then spraying the mixture to obtain the mixture;

[0066] S3, pressing the mixed material into a compact to obtain a green compact;

[0067] S4. Place the pressed green sheet in a sintering furnace, raise the temperature to the forming agent removal temperature according to a predetermined sintering process, and after removing the forming agent, perform micro-pressure atmosphere sintering. During the sintering process, part of the metal particles in the metal reinforcing agent react with carbon and precipitate fine dispersion-strengthened hard phase precipitates. The dispersion-strengthened hard phase precipitates are dispersed in the hard phase. At the same time, another part of the metal particles in the metal reinforcing agent are dissolved in the bonding phase to form a solid solution-strengthened bonding phase, and finally a high-strength and toughness metal ceramic is obtained.

[0068] Preferably, in step S1, the metal reinforcement raw material comprises metal powders, oxides, complexes, salts or any combination thereof of at least two metal elements selected from tantalum, niobium, manganese, ruthenium, rhenium, yttrium and cerium.

[0069] Preferably, in step S1, the metal strengthener raw material is mixed with a forming agent and a solvent, crushed by ball milling, dried and processed, and then subjected to hydrogen reduction treatment to obtain ultrafine metal particles as the metal strengthener, and the particle size of the metal strengthener is 100-500 nm.

[0070] Preferably, in step S1, the hydrogen reduction temperature is 400-800°C.

[0071] Preferably, in steps S1 and S2, the molding agent is selected from at least one of 48#~56# paraffin wax and PEG1000~PEG20000; and the solvent is selected from at least one of anhydrous ethanol and deionized water.

[0072] Preferably, in step S2, the amount of the metal reinforcement added is 0.5-5wt% of the total amount of the metal ceramic, preferably 1.2-3.6%.

[0073] Preferably, in step S4, the atmosphere in the sintering furnace during the forming agent removal process is a hydrogen atmosphere or a vacuum atmosphere:

[0074] In step S1, the metal reinforcement raw material is subjected to hydrogen reduction treatment, and the atmosphere in the sintering furnace during the forming agent removal process is a vacuum atmosphere;

[0075] In step S1, when the metal reinforcing agent raw material is directly used, the atmosphere in the sintering furnace during the forming agent removal process is a hydrogen atmosphere.

[0076] Preferably, in step S4, the micro-pressure atmosphere sintering is specifically as follows: after heating to temperature A, introducing a process gas of x mbar, then heating and sintering to temperature B in a nitrogen atmosphere at a heating rate of 2~10℃ / min, then switching to vacuum sintering, keeping at temperature B for 0.5~3h, then cooling to 1200℃ in a process gas partial pressure atmosphere of y mbar, and finally high-pressure cooling in an argon atmosphere; wherein, temperature A is 1000~1400℃, temperature B is 1400~1600℃, x is 0.5~60, y is 10~100, and the process gas is at least one selected from nitrogen, argon, and helium.

[0077] According to another aspect of the present invention, the present invention provides the following technical solution:

[0078] A cutting tool comprises a substrate, wherein the substrate is composed of the metal ceramic or the metal ceramic prepared according to the preparation method.

[0079] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0080] Example 1

[0081] A method for preparing a high-strength and high-toughness metal ceramic comprises the following steps:

[0082] S1. Mix equal amounts of tantalum and niobium oxides in a mass ratio of 2:1, add PEG2000, ball mill with anhydrous alcohol for 20 hours, spray dry, and then reduce and sinter at 700°C in a continuous pusher furnace under a hydrogen atmosphere to obtain ultrafine metal particles as a metal strengthening agent;

[0083] S2, select metal reinforcement agent, cobalt / nickel binding phase powder, titanium-containing cubic carbonitride powder, molybdenum carbide powder and tungsten, tantalum, niobium carbide powder, tungsten carbide as raw materials, the mass percentage of each raw material is: metal reinforcement agent 1.5wt%, cobalt / nickel binding phase powder 15wt%, titanium-containing cubic carbonitride powder 50wt%, tungsten, tantalum, niobium solid solution carbide 15wt%, molybdenum carbide powder 2wt%, the balance is tungsten carbide, the total mass percentage of each raw material is 100wt%, and the powder particle size is <1.8 μm; ball mill the metal reinforcement agent, cobalt / nickel binding phase powder, titanium-containing cubic carbonitride powder, tungsten, tantalum, niobium solid solution carbide, molybdenum carbide powder, tungsten carbide and molding agent, use paraffin as molding agent (content is 2.0 wt%), use anhydrous ethanol as solvent, and dry after ball milling to obtain a mixed powder;

[0084] S3, pressing the mixed material into a compact to obtain a green compact;

[0085] S4. Place the pressed green sheet in a vacuum atmosphere, heat it to the forming agent removal temperature, and remove the forming agent; place the pressed green sheet from which the forming agent has been removed in a vacuum atmosphere, heat it to 1150°C, introduce 50 mbar nitrogen, and then heat it to 1450°C in a nitrogen atmosphere at a heating rate of 6°C / min, then switch to vacuum sintering, keep it at 1450°C for 1.5 hours, and then cool it to 1200°C in a 30 mbar argon atmosphere, and finally cool it to room temperature under high pressure in an argon atmosphere to obtain a metal ceramic.

[0086] Example 2

[0087] A method for preparing a high-strength and high-toughness metal ceramic comprises the following steps:

[0088] S1. Use equal amounts of tantalum and niobium oxides in a tantalum: niobium mass ratio of 2:1 as metal strengthening agents;

[0089] S2. Select tantalum, niobium oxides, cobalt / nickel binder phase powder, titanium-containing cubic carbonitride powder, molybdenum carbide powder and tungsten, tantalum, niobium solid solution carbides, tungsten carbide in an equivalent amount of tantalum: niobium mass ratio of 2:1 as raw materials. The mass percentage of each raw material is: oxide powder with an equivalent metal content of 1.5wt% tantalum and niobium (tantalum, niobium mass ratio 2:1), cobalt / nickel binder phase powder 15 wt%, titanium-containing cubic carbonitride powder 50wt%, tungsten, tantalum, niobium solid solution carbides 15wt%, molybdenum carbide powder 2wt%, and the remainder is tungsten carbide. The total mass percentage of each raw material is 100wt%, and the powder particle size is <1.8 μm; ball-milling ultrafine metal powder, cobalt / nickel binder phase powder, titanium-containing cubic carbonitride powder, solid solution carbides of tungsten, tantalum and niobium, molybdenum carbide powder, tungsten carbide and a molding agent, using paraffin as a molding agent (content of 2.0wt%), using anhydrous ethanol as a solvent, and drying after ball-milling to obtain a mixed powder;

[0090] S3, pressing the mixed material into a compact to obtain a green compact;

[0091] S4. Place the pressed green sheet in a hydrogen atmosphere, raise the temperature to 700°C, a forming agent removal temperature, to remove the forming agent; raise the temperature of the pressed green sheet from which the forming agent has been removed to 1150°C in a vacuum atmosphere, introduce 50 mbar nitrogen, and then sinter the green sheet to 1450°C at a heating rate of 6°C / min in a nitrogen atmosphere, then switch to vacuum sintering, keep the temperature at 1450°C for 1.5 hours, and then cool it to 1200°C in a 30 mbar argon atmosphere, and finally cool it to room temperature under high pressure in an argon atmosphere to obtain a metal ceramic.

[0092] Example 3

[0093] A method for preparing a high-strength and high-toughness metal ceramic comprises the following steps:

[0094] S1. Select tantalum oxide and ammonium rhenate in a tantalum:rhenium mass ratio of 1:1, add PEG2000, ball mill with anhydrous alcohol for 20 hours, spray dry, and then reduce and sinter at 700°C in a continuous push plate furnace under a hydrogen atmosphere to obtain ultrafine metal particles as a metal strengthening agent;

[0095] S2, select metal reinforcement, cobalt / nickel binding phase powder, titanium-containing cubic carbonitride powder, molybdenum carbide powder and tungsten, tantalum, niobium carbide powder as raw materials, the mass percentage of each raw material is: metal reinforcement 2wt%, cobalt / nickel binding phase powder 15wt%, titanium-containing cubic carbonitride powder 55wt%, tungsten, tantalum, niobium solid solution carbide 10wt%, molybdenum carbide powder 1.8wt%, the balance is tungsten carbide, the total mass percentage of each raw material is 100wt%, and the powder particle size is <1.8 μm; ball mill the metal reinforcement, cobalt / nickel binding phase powder, titanium-containing cubic carbonitride powder, tungsten, tantalum, niobium solid solution carbide, molybdenum carbide powder, tungsten carbide and molding agent, use paraffin as molding agent (content is 2.0wt%), use anhydrous ethanol as solvent, dry after ball milling, and obtain a mixed powder;

[0096] S3, pressing the mixed material into a compact to obtain a green compact;

[0097] S4. Place the pressed green sheet in a vacuum atmosphere, heat it to the forming agent removal temperature, and remove the forming agent; place the pressed green sheet from which the forming agent has been removed in a vacuum atmosphere, heat it to 1150°C, introduce 50 mbar nitrogen, and then heat it to 1450°C in a nitrogen atmosphere at a heating rate of 6°C / min, then switch to vacuum sintering, keep it at 1450°C for 1.5 hours, and then cool it to 1200°C in a 30 mbar argon atmosphere, and finally cool it to room temperature under high pressure in an argon atmosphere to obtain a metal ceramic.

[0098] Example 4

[0099] A method for preparing a high-strength and high-toughness metal ceramic comprises the following steps:

[0100] S1. Tantalum oxide, yttrium oxide and manganese carbonate are mixed in equal proportions with a mass ratio of tantalum: yttrium: manganese of 1:1:1, PEG2000 is added, ball-milled with anhydrous alcohol for 20 hours and then spray-dried, and then reduced and sintered at 700°C in a continuous push-plate furnace under a hydrogen atmosphere to obtain ultrafine metal particles as a metal strengthening agent;

[0101] S2, select metal reinforcement, cobalt / nickel binding phase powder, titanium-containing cubic carbonitride powder, molybdenum carbide powder and tungsten, tantalum, niobium carbide powder as raw materials, the mass percentage of each raw material is: metal reinforcement 1.5wt%, cobalt / nickel binding phase powder 15wt%, titanium-containing cubic carbonitride powder 52.5wt%, tungsten, tantalum, niobium solid solution carbide 10wt%, molybdenum carbide powder 2wt%, the balance is tungsten carbide, the total mass percentage of each raw material is 100wt%, and the powder particle size is <1.8 μm; ball mill the metal reinforcement, cobalt / nickel binding phase powder, titanium-containing cubic carbonitride powder, tungsten, tantalum, niobium solid solution carbide, molybdenum carbide powder, tungsten carbide and molding agent, use paraffin as molding agent (content is 2.0wt%), use anhydrous ethanol as solvent, dry after ball milling, and obtain a mixed powder;

[0102] S3, pressing the mixed material into a compact to obtain a green compact;

[0103] S4. Place the pressed green sheet in a vacuum atmosphere, heat it to the forming agent removal temperature, and remove the forming agent; place the pressed green sheet from which the forming agent has been removed in a vacuum atmosphere, heat it to 1150°C, introduce 50 mbar nitrogen, and then heat it to 1450°C in a nitrogen atmosphere at a heating rate of 6°C / min, then switch to vacuum sintering, keep it at 1450°C for 1.5 hours, and then cool it to 1200°C in a 30 mbar argon atmosphere, and finally cool it to room temperature under high pressure in an argon atmosphere to obtain a metal ceramic.

[0104] Comparative Example 1

[0105] The difference from Example 1 is that step S1 is not performed, Co powder and Ni powder with a mass ratio of 1:1 are used as the binder phase composite powder, and the metal ceramic material is prepared by adding the same mass fraction of each component element in the form of its carbide.

[0106] For the metal ceramic materials obtained in each embodiment and comparative example, the sample materials were cut in half using a "Discotom-100 metallographic cutting machine", and then placed in an "AbraPol-20 automatic microprocessor-controlled vertical grinding and polishing machine" by hot mounting with phenolic resin in a "Citopress-20 semi-automatic hot mounting machine" for sample preparation. After grinding and polishing with 80 mesh, 220 mesh, 500 mesh, 1200 mesh, and 4000 mesh, the samples were measured for Vickers hardness HV and crack toughness Kic on an "FLC50V-ARS9000 fully automatic micro-Vickers hardness tester", and the results are shown in the following table.

[0107]

[0108] The metal ceramic materials obtained in each embodiment and comparative example are cut and formed to form a rough cutter blank. A nylon brush containing SiC is used to round the cutting edge of the cutter. A PVD / CVD coating is formed on the surface of the rough cutter blank to obtain a coated metal ceramic cutter.

[0109] The comparative test data and test results of the coated metal ceramic cutting tools of each embodiment and comparative example under different cutting conditions are as follows:

[0110] The wear resistance of the above tools was compared and tested by longitudinal turning of 40CrNi2Mo steel bars. The tool life standard is the machining time when the back tool wear is 0.3mm. The cutting conditions are shown in the table below:

[0111]

[0112] The test results are detailed in the table below:

[0113]

[0114] The test results show that: in the continuous cutting condition of steel, the wear resistance and the tool tip toughness of the samples of the embodiment of the present invention are significantly improved compared with the samples of the comparative example. It can be proved that the cutting tool of the embodiment of the present invention can effectively improve the room temperature toughness and high temperature thermal vibration resistance of the material.

[0115] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A high-strength and toughness metal ceramic, characterized in that: It is composed of a hard phase, a bonding phase and a metal reinforcement; The hard phase is mainly composed of (1) carbide, nitride, nitride carbide or any combination thereof of titanium, and (2) carbide, nitride, nitride carbide or any combination thereof of at least one metal element in Groups IVB, VB, and VIB of the periodic table except titanium, and (1) and (2) are not nitrides at the same time; The bonding phase is at least two of the transition metals cobalt, nickel and iron; The metal strengthener is at least two of tantalum, niobium, manganese, ruthenium, rhenium, yttrium, and cerium and contains at least one of tantalum, niobium, and manganese; the metal strengthener is distributed in the microstructure of the metal ceramic in a refined and uniformly dispersed state; wherein, in the hard phase, there are dispersion-strengthened hard phase precipitates formed by the reaction of part of the metal elements in the metal strengthener with carbon and precipitated, and the dispersion-strengthened hard phase precipitates contain at least one of tantalum carbide and niobium carbide; another part of the metal elements in the metal strengthener are solid-dissolved in the bonding phase to form a solid-solution-strengthened bonding phase.

2. The high-strength and toughness metal ceramic according to claim 1, characterized in that: The binder phase accounts for 10-24wt% of the total amount of the metal ceramic, and the hard phase accounts for 76-90wt% of the total amount of the metal ceramic.

3. The high-strength and toughness metal ceramic according to claim 1, characterized in that: The particle size of the hard phase is 0.5-5.0 μm.

4. The high-strength and toughness metal ceramic according to claim 1, characterized in that: Tantalum accounts for 0.35-6.0wt% of the total amount of the metal ceramic, niobium accounts for 0.2-2.0wt% of the total amount of the metal ceramic, and manganese accounts for 0.3-4.0wt% of the total amount of the metal ceramic.

5. The high-strength and toughness metal ceramic according to claim 1, characterized in that: The mass ratio of tantalum and niobium added to the binder phase is (1-4):

1.

6. The high-strength and toughness metal ceramic according to claim 1, characterized in that: The manganese added to the binder phase accounts for ≤50wt% of the metal reinforcement.

7. The high-strength and toughness metal ceramic according to claim 1, characterized in that: In the same scanning electron microscope photograph, the hard phase includes a first hard phase and a second hard phase, wherein the first hard phase mainly appears as a phase with a black core-gray outer ring structure and a phase with a black-gray structure, and the first hard phase is mainly titanium carbide and / or titanium nitride and / or titanium nitride carbide, and the second hard phase mainly appears as a phase with a bright core-gray outer ring structure; the bonding phase mainly appears as a phase with a medium brightness structure, and there are a large number of point-precipitated micro-nano precipitate phases at the interface between the bonding phase and the hard phase.

8. The method for preparing the high-strength and toughness metal ceramic according to any one of claims 1 to 7, characterized in that: The steps include: S1. Prepare metal strengthening agent raw materials; S2, prepare hard phase powder and binder phase powder, the hard phase powder mainly consisting of (1) titanium carbide, nitride, nitride carbide or any combination thereof, and (2) carbide, nitride, nitride carbide or any combination thereof of at least one metal element in Groups IVB, VB, and VIB of the periodic table except titanium, and (1) and (2) are not nitrides at the same time; the binder phase powder is at least two of the transition metals cobalt, nickel and iron, then, mix the hard phase powder, the binder phase powder, the metal reinforcing agent raw material in step S1, the solvent and the forming agent, perform ball milling again, and obtain a mixed material by spraying; S3, pressing the mixed material into a compact to obtain a green compact; S4. Place the green compact in a sintering furnace, heat it to the forming agent removal temperature, and after removing the forming agent, perform micro-pressure atmosphere sintering to obtain a high-strength and toughness metal ceramic; the micro-pressure atmosphere sintering is specifically as follows: after heating to temperature A, introduce a process gas of x mbar, then heat and sinter to temperature B in a nitrogen atmosphere at a heating rate of 2-10°C / min, then switch to vacuum sintering, keep at temperature B for 0.5-3h, then cool to 1200°C in a process gas partial pressure atmosphere of y mbar, and finally perform high-pressure cooling in an argon atmosphere; wherein, temperature A is 1000-1400°C, temperature B is 1400-1600°C, x is 0.5-60, y is 10-100, and the process gas is at least one selected from nitrogen, argon, and helium.

9. The method for preparing a high-strength and toughness metal ceramic according to claim 8, characterized in that: In step S1, the metal reinforcement raw material is metal powder, oxide, complex, salt or any combination thereof of at least two metal elements selected from tantalum, niobium, manganese, ruthenium, rhenium, yttrium and cerium.

10. The method for preparing high-strength and toughness metal ceramic according to claim 9, characterized in that: In step S1, the metal strengthening agent raw material is mixed with a forming agent and a solvent, crushed by ball milling, dried and processed, and then subjected to hydrogen reduction treatment to obtain ultrafine metal particles as the metal strengthening agent.

11. The method for preparing a high-strength and toughness metal ceramic according to claim 10, characterized in that: In step S4, the atmosphere in the sintering furnace during the forming agent removal process is a hydrogen atmosphere or a vacuum atmosphere: In step S1, the metal reinforcement raw material is subjected to hydrogen reduction treatment, and the atmosphere in the sintering furnace during the forming agent removal process is a vacuum atmosphere; In step S1, when the metal reinforcing agent raw material is directly used, the atmosphere in the sintering furnace during the forming agent removal process is a hydrogen atmosphere.

12. A cutting tool, characterized in that: The invention comprises a matrix, wherein the matrix is ​​composed of the high-strength and toughness metal ceramic according to any one of claims 1 to 7 or the high-strength and toughness metal ceramic prepared by the preparation method according to any one of claims 8 to 11.

Citation Information

Patent Citations

  • Metal ceramic and preparation method thereof

    CN116162838A

  • Hard alloy and preparation method thereof

    CN117701968A

  • Cermet and manufacturing method thereof

    JP2009108338A